New simulation of symmetrical three phase induction motor under transformations of park (1999)
ABSTRACT: The induction motor itself is a very superior electric motor, being simple and robust in structure, easy to maintain and very reliable. This paper shows that it is possible to use currently available commercial software to easily simulate a symmetrical three-phase induction machine. The components of a typical induction machine are introduced and a method to incorporate these in the MATLAB/SIMULINK software package is given. The computer simulation for various modes of operation is conveniently obtained from the equation that describes the symmetrical induction motor in an arbitrary reference frame. This simulation would be useful to study the performance of the induction machine when used in conjuction with electronic switching devices. The motor is studied under free acceleration, variable loads and open phases. This model is valid for most of the common machines.